PENGEMBANGAN MATERIAL RINGAN SERAT GELAS PADA INDUSTRI KERETA API - Oki Kurniawan; Willy Artha Wirawan; Akbar Zulkarnain (Jurnal Transportasi, 2019)
Abstract The use of composite materials has been developed in the railroad transportation industry sector in Indonesia. For example, PT INKA has used composite materials with fiber glass reinforcement. The purpose of this study is to determine the characteristics of tensile strength and bending strength of the composite material so that it can be proposed to be further developed and utilized by the manufacturing industry, especially the railroad industry. In this study, 4 types of matrix variations were examined, namely epoxy, repoxy, polyester, and bhispenol using fiber glass reinforcement. Tensile strength and bending strength tests were performed in accordance with the ASTM D-638 and the ASTM D-790 standards, respectively. The results of this study indicate that the variation of the matrix is very influential on the tensile strength and bending strength of composite materials. Keywords: composite material, glass fiber, tensile strength, bending strength  Abstrak Penggunaan material komposit mulai banyak dikembangkan di sektor industri trasportasi kereta api di Indone-sia. Sebagai contoh, PT INKA sudah menggunakan material komposit dengan penguat serat gelas. Tujuan penelitian ini adalah untuk mengetahui karakteristik kekuatan tarik dan kekuatan bending material komposit agar dapat diusulkan untuk lebih dikembangkan dan dimanfaatkan oleh industri manufaktur, khususnya industri kereta api. Pada penelitian ini digunakan 4 jenis variasi matriks, yaitu epoxy, repoxy, polyester, dan bhispenol dengan menggunakan penguat serat gelas. Pengujian kekuatan tarik menggunakan standar ASTM D-638 dan pengujian bending menggunakan standar ASTM D-790. Hasil studi ini menunjukkan bahwa variasi matriks sangat berpengaruh pada kekuatan tarik maupun kekuatan bending material komposit. Kata-kata kunci: material komposit, serat gelas, kekuatan tarik, kekuatan bending